LA CLÁUSULA QUE HABILITA A LA EMPRESA DE MEDICINA PREPAGA A INCREMENTAR EL VALOR DE LA CUOTA EN BASE A LA EDAD DEL AFILIADO: SU ENCUADRE EN LA ENUMERACIÓN DEL ART. 37 DE LA LEY 24.240 DE ARGENTINA - Florencia Vazzano (Revista Internacional de Doctrina y Jurisprudencia, 2015)
In this paper we focus on the contract clause prepaid medical why the utility company unilaterally has the power to increase the share of affiliate because of their older age. Their analysis will be from the list of unfair terms of art. 37 inc. b of the Law 24,240 on Consumer and effects provided by this law, and the law 26,682 which establishes the regulatory framework for prepaid medicine companies.Also, select Argentina jurisprudence has declared the nullity of such clause considered abusive and harmful for the right to health of the affiliated company, which has constitutional right. Keywords: